ACENOCOUMAROL OR WARFARIN: WHICH IS THE CLINICIAN’S ALLY? - Rao N, Karthik; Patil, Navin; Avinash, A; Hande, Handattu Manjunatha; Kunder, Sushil Kiran; Rao, Raghavendra (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Warfarin and acenocoumarol are commonly prescribed oral anticoagulant drugs that are used in the prevention and treatment of thromboembolic disorders across the world. Although both these drugs act by a similar mechanism, there are significant differences between them, especially in terms of their half-lives, and more importantly, in their variability in response pharmacogenetically. This case report highlights an instance wherein warfarin proved to provide a much more stable anticoagulant cover, as compared to that provided by acenocoumarol. Keywords: Thrombosis, Bleeding, Antiphospholipid antibody syndrome, Anticoagulant, International normalized ratio.